Method and application of in-situ growth of a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode

By growing a composite film of an aluminum bottom electrode, a wurtzite aluminum nitride-based film and an ultra-thin alumina protective layer in situ in the same vacuum chamber, the pore and heterogeneous metal doping problems between the bottom electrode and the AlN-based film are solved, and high-performance and stable piezoelectric and ferroelectric devices are achieved.

CN115652271BActive Publication Date: 2025-03-28DALIAN CHIP MATERIALS & THIN FILM TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211423044.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2025-03-28
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

In the prior art, there are pores, holes and heterogeneous metal elements doping problems between the aluminum bottom electrode and the wurtzite aluminum nitride-based film, resulting in poor device performance; at the same time, the AlN-based film is prone to dehydration and oxidation, affecting the stability of the device.

Method used

The physical vapor deposition (PVD) method was used to continuously grow in situ in the same vacuum chamber (111) textured aluminum bottom electrode, (0002) textured wurtzite aluminum nitride based film and ultra-thin alumina protective layer composite film. By optimizing process parameters, we ensure the texture consistency of the bottom electrode and the AlN-based film, and in-situ oxidize the Al metal film into an Al2O3 protective layer in the same chamber, completely covering the AlN-based film.

Benefits of technology

The problems of bottom electrode surface pollution and pores and holes between the two films are solved, and the heterogeneous metal doping and deliquesting oxidation of the AlN-based film are avoided, which significantly improves the piezoelectric and ferroelectric properties and stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115652271B_ABST
    Figure CN115652271B_ABST
Patent Text Reader

Abstract

The present invention provides a method and application for in-situ growth of a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode. The same Al metal target is used to deposit a (111) textured Al metal bottom electrode on a substrate, and then the deposition atmosphere and other process parameters are changed to achieve in-situ continuous growth of the (111) textured Al bottom electrode film and the (0002) textured wurtzite AlN-based film. The Al metal target is continued to be used to in-situ grow an Al metal film on the surface of the wurtzite AlN-based film, and finally the Al metal film is in-situ oxidized into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder. The present invention can solve the problems of the bottom electrode surface being easily contaminated, pores and voids being easily formed between the two films, and the AlN-based film being easily doped with heterogeneous metal elements when preparing the bottom electrode / AlN-based film by the traditional non-in-situ continuous method, and solve the problem of the AlN-based film being easily deliquescent and oxidized; the operation is simple and easy, and the engineering practicability is strong.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic information technology and relates to a method for in-situ growing a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode. Background Art

[0002] Wurtzite AlN films with crystal plane texture (c-axis preferred growth orientation) are widely used in high-frequency surface acoustic wave (SAW) filters, bulk acoustic wave (BAW) filters, MEMs sensors and other devices due to their excellent piezoelectric properties, high breakdown field strength, high thermal conductivity, high temperature stability, high acoustic wave transmission rate and other characteristics. In recent years, Sc doping has been found to significantly improve the piezoelectric properties of AlN films; in addition, wurtzite AlN films doped with elements such as Sc, B, and Y have also been shown to have excellent ferroelectric properties and can be used in the preparation of devices such as ferroelectric enhanced high electron mobility transistors and ferroelectric memories.

[0003] Wurtzite AlN-based films for certain piezoelectric and ferroelectric device applications are generally first deposited on a bottom electrode film such as platinum (Pt), molybdenum (Mo), titanium nitride (TiN), or tantalum nitride (TaN) with (111) texture grown on the substrate surface, and the (111) crystal plane texture of the bottom electrode film is used to induce the wurtzite AlN-based film to have a (0002) textured structure; then a patterned metal top electrode is prepared on the surface of the AlN-based film using a hard mask or a photolithography process to form a metal-dielectric-metal (MIM) structure device. When the above-mentioned MIM structure device is prepared using physical vapor deposition (PVD) technology, it is necessary to first place the substrate in a vacuum device or a vacuum chamber to deposit a (111) textured bottom electrode film, and then transfer it to another vacuum device or another vacuum chamber to deposit a (0002) textured AlN-based film using a metal target such as Al in an Ar, N2 mixed atmosphere or a pure N2 atmosphere. After that, it is removed from the vacuum chamber, and a hard mask is covered on the surface of the AlN-based film or a photolithography patterning process is performed, and finally it is placed in the vacuum chamber again to prepare the metal upper electrode. The sample transfer process destroys the continuity of the film growth, is time-consuming, and has low production efficiency; at the same time, the above transfer process is prone to cause contamination of the bottom electrode surface, and pores and voids appear between the bottom electrode and the AlN-based film, resulting in poor performance of the device. Even if the bottom electrode film is first deposited using metal targets such as Pt, Mo, and Ti in the same vacuum chamber, and then the AlN-based film is grown on the bottom electrode using metal targets such as Al, the deposition process of the bottom electrode film will inevitably cause contamination of the Al target, as well as the attachment of foreign metals and transition metal nitrides to the vacuum chamber wall, sample stage, etc., resulting in the subsequent growth of the AlN-based film containing foreign metal elements doped, resulting in poor performance of the film and device. In addition, before preparing the metal upper electrode, the AlN-based film has to be removed from the vacuum environment for a short time and exposed to the atmosphere. Studies have shown that the surface of AlN is extremely active and can easily absorb water vapor in the air to undergo a hydrolysis reaction (AlN+3H2O=Al(OH)3↓+NH3↑), and react with oxygen in the air to form aluminum oxynitride (AlN 1-x O x The above reaction leads to the appearance of an interfacial layer with a thickness of several nanometers and rich in high concentration of oxygen impurities and nitrogen vacancies between the AlN-based film and the subsequently grown upper electrode. Oxygen and nitrogen vacancies act as donor doping to give the interfacial layer n + Due to the degenerate semiconductor characteristics, the electrons emitted by the metal upper electrode can tunnel through the interface layer into the AlN-based film, resulting in an increase in the leakage current of the device and a deterioration in the anti-breakdown characteristics. Summary of the invention

[0004] In order to overcome the above-mentioned process and device performance problems of preparing the bottom electrode\AlN-based film\top electrode, the present invention proposes to use physical vapor deposition (PVD) to continuously grow (111) textured aluminum bottom electrode, (0002) textured wurtzite aluminum nitride-based piezoelectric ferroelectric film and ultra-thin aluminum oxide protective layer composite film in the same vacuum chamber. The specific method is to first use single Al metal as the target material, and in a pure Ar atmosphere, use magnetron sputtering or laser pulse deposition technology to deposit Al electrode film on the substrate, and optimize the process parameters to make the Al electrode film have a (111) textured structure; then use Al as the main component target, Sc, Y, B, etc. as doping element targets, and in Ar, N2 mixed atmosphere or pure N2 atmosphere, use magnetron sputtering or laser pulse deposition technology to in-situ deposit AlN-based film on the Al electrode film, and use the (111) crystal plane texture of the Al electrode film to induce the AlN-based film to have a (0002) textured structure, so that it has excellent piezoelectric and ferroelectric properties. Then, using Al metal as the target, a metal Al film with a thickness of 2-5 nanometers is in situ deposited on the surface of the AlN-based film by magnetron sputtering or laser pulse technology in a pure Ar atmosphere. Finally, the metal Al film is in situ oxidized in the same vacuum chamber to transform it into an amorphous, dense Al2O3 thin layer that completely covers the AlN-based piezoelectric and ferroelectric films underneath.

[0005] (111) The work function of the textured Al metal electrode film is 4.26 eV, which is comparable to the work function of commonly used electrode materials such as TiN and Mo, and can form a Schottky contact with an AlN-based film with a relatively high barrier height. Al2O3 film has excellent chemical stability and will not react with water vapor in the atmosphere or the upper electrodes such as metals and transition metal nitrides that will be prepared later. At the same time, the band gap of the Al2O3 film is as high as 8.9 eV (higher than 6.2 eV of AlN), and after contacting with the upper electrode, it will form a Schottky contact with an extremely high barrier height. According to semiconductor physics theory, this type of interface contact can greatly reduce the leakage current and increase the device's breakdown voltage. The relative dielectric constant (e) of Al2O3 is r ) is 9, which is almost the same as AlN. The thickness of the Al2O3 film prepared by the present invention is 2-5 nanometers, while the thickness of the AlN-based film with excellent piezoelectric and ferroelectric properties is generally greater than 50 nanometers. When forming a metal-Al2O3 film / AlN-based film-metal (MIM) structure device, the capacitor (C1) formed by the Al2O3 film and the capacitor (C2) formed by the AlN-based film are in a series relationship with equal areas. The capacitance formula is C=e0e r A / d, where A is the area of ​​the capacitor, d is the thickness of the dielectric film, e0 is the vacuum dielectric constant, and e ris the relative dielectric constant of the dielectric film. Since the thickness of the Al2O3 film is much smaller than that of the AlN-based film, C1 is much larger than C2. According to the voltage-dividing principle of the series capacitor, most of the applied voltage will be applied to the AlN-based film (> 90%), and the voltage-dividing of the Al2O3 film is extremely small, thus ensuring the piezoelectric and ferroelectric properties of the AlN-based film and avoiding the breakdown of the Al2O3 film.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for in-situ growth of a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode, wherein a (111) textured Al metal bottom electrode is deposited on a substrate using the same Al metal target, and then the deposition atmosphere and other process parameters are changed to achieve in-situ continuous growth of the (111) textured Al bottom electrode film and the (0002) textured wurtzite AlN-based film. The Al metal target is continued to be used to in-situ grow an Al metal film on the surface of the wurtzite AlN-based film, and finally the Al metal film is in-situ oxidized into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films underneath. This method not only solves the problems of the bottom electrode surface being easily contaminated, pores and voids being easily formed between the two films, and the AlN-based film being easily doped with heterogeneous metal elements when preparing the bottom electrode / AlN-based film by the traditional non-in-situ continuous method, but also solves the problem of the AlN-based film being easily deliquescent and oxidized when subsequently growing a patterned top electrode. The operation is simple and easy, and the engineering practicability is strong. At the same time, the high work function characteristics of the Al metal electrode film, the excellent dielectric properties of the Al2O3 layer and the voltage division principle of the series capacitor are utilized to reduce the leakage current of the device, improve the breakdown voltage, and ensure the working voltage division of the AlN-based piezoelectric ferroelectric film. The physical mechanism is clear.

[0008] A method for in-situ growing a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode, specifically comprising the following steps:

[0009] Step 1: Clean the substrate to remove organic contamination, metal particles and other impurities on the surface. The substrate is made of one of III-V semiconductor materials such as sapphire, Si, Ge or GaN.

[0010] Step 2: The same Al metal target is used throughout the process. In a pure Ar atmosphere, the Al electrode film is deposited on the substrate by magnetron sputtering technology. The Al electrode film has a (111) texture structure by adjusting the process parameters. Then, in the same chamber, Sc, Y, B, etc. are added as doping element targets. In an Ar, N2 mixed atmosphere or a pure N2 atmosphere, the AlN-based film is in-situ deposited on the Al electrode film by magnetron sputtering technology. The (111) crystal plane texture of the Al electrode film is used to induce the wurtzite AlN-based film to have a (0002) texture structure. Then, the magnetron sputtering technology is continued in the same chamber. In a pure Ar atmosphere, a metal Al film with a thickness of 2-5 nanometers is in-situ deposited on the surface of the AlN-based film by magnetron sputtering technology. Finally, the metal Al film is in-situ oxidized in the same vacuum chamber to transform it into an amorphous, dense Al2O3 thin layer that completely covers the wurtzite AlN-based piezoelectric and ferroelectric film underneath.

[0011] The magnetron sputtering technology can be replaced by laser pulse deposition technology and the like.

[0012] The thickness of the Al metal film used as the bottom electrode material is 50-200 nm.

[0013] The thickness of the AlN-based film is 50-1500 nm.

[0014] The thickness of the Al2O3 thin layer is 2-5 nm.

[0015] The process parameters include target-substrate distance, ratio of argon to nitrogen, sputtering power, substrate temperature, working gas pressure, etc.

[0016] The specific process parameters for depositing (111) textured Al bottom electrode material are: target-substrate distance is 80~120 mm; Ar gas flow rate is 20~50 sccm; sputtering power: 100~200 W; substrate temperature is room temperature~400 ℃; working gas pressure is 0.3~1.0 Pa; sputtering time: 5-20 min.

[0017] The specific process parameters for depositing wurtzite aluminum nitride-based films with (0002) textured microstructure are: target-substrate distance is 80-120 mm; Ar:N2=(0-20): (20-50) sccm; sputtering power: 50-300 W; substrate temperature is room temperature ~ 400 ℃; working gas pressure is 0.4~0.8 Pa; sputtering time: 30-200 min.

[0018] The specific process parameters for depositing metal aluminum film on the surface of aluminum nitride-based film are as follows: the target material is a single metal aluminum target, the target-substrate distance is 80~120 mm; Ar gas flow rate is 20-50 sccm; sputtering power: 50-80 W; substrate temperature is room temperature~400 ℃; working gas pressure is 0.4~0.8 Pa; sputtering time: 1-3 min.

[0019] The in-situ oxidation treatment process includes thermal oxidation by introducing high-purity oxygen into the vacuum chamber and heating the sample stage, and plasma oxidation by discharging and ionizing the high-purity oxygen introduced into the vacuum chamber.

[0020] The specific process parameters of the in-situ oxidation treatment are: the vacuum chamber is maintained at a negative pressure state below one atmosphere, the substrate temperature is room temperature ~ 400 ° C, and the oxidation time is 1-3 min.

[0021] A composite film with a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer grown in situ on an aluminum bottom electrode is obtained by using the above preparation method.

[0022] The invention discloses an application of a composite film with an in-situ growth of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode, and a top electrode is prepared on the surface of the composite film by thermal evaporation or sputtering to obtain a metal-dielectric-metal (MIM) structure capacitor. The piezoelectric-ferroelectric performance of the capacitor is tested using a piezoelectric-ferroelectric tester.

[0023] The top electrode is made of one of highly conductive metals such as Au, Pt, Mo and TiN.

[0024] The thickness of the top electrode is 80-150 nm.

[0025] The beneficial effects of the present invention are as follows: the present invention provides a method for in-situ growth of a (0002) textured wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer composite film on a (111) textured aluminum bottom electrode for an electronic device, wherein the same Al metal target is used throughout the process, and the (111) textured Al metal bottom electrode is first deposited on a substrate, and then in the same chamber, process parameters such as the deposition atmosphere are changed to achieve in-situ continuous growth of the (111) textured Al bottom electrode film and the (0002) textured wurtzite AlN-based film. In the same chamber, an Al metal film is in-situ grown on the surface of the wurtzite AlN-based film, and finally the Al metal film is in-situ oxidized into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder. Compared with other traditional metal-dielectric-metal (MIM) structure device preparation technologies, this technology avoids the problems of doping with foreign metal elements and deliquescent oxidation in AlN-based films, providing a reliable guarantee for the performance of the device. At the same time, it has the significant advantages of simple process, strong controllability and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A flow chart of in-situ growth of a (0002) textured wurtzite aluminum nitride-based film and an aluminum oxide protective layer on a (111) textured aluminum bottom electrode in the method of the present invention;

[0027] Figure 2 The Al bottom electrode with (111) texture and the wurtzite Al with (0002) texture grown in situ by magnetron sputtering in Example 1 are 0.7 Sc 0.3 N film, Pt as top electrode, leakage current curve of thin film capacitor;

[0028] Figure 3 In Example 2, (111) textured Pt is used as the bottom electrode and the top electrode, and (0002) textured wurtzite Al 0.9 Sc 0.1 Leakage current curve of the sample with in-situ growth of ultra-thin aluminum oxide protective layer on the surface of N film;

[0029] Figure 4 The wurtzite Al with (0002) texture is in situ grown on the Al bottom electrode with (111) texture by magnetron sputtering in Example 1. 0.7 Sc 0.3 N film and aluminum oxide protective layer, Pt as the top electrode, leakage current curve of the thin film capacitor;

[0030] Figure 5 The wurtzite Al with (0002) texture is in situ grown on the Al bottom electrode with (111) texture by magnetron sputtering in Example 2. 0.9 Sc 0.1 N film and Al2O3 protective layer, Pt as the top electrode, leakage current curve of the thin film capacitor. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the operation process of the present invention is further described in detail below with reference to the accompanying drawings and specific examples. It should be noted that the specific examples described herein are only used to explain the present invention, and the illustrations are for schematic purposes only and are not intended to limit the scope of the present invention.

[0032] In this comparative example, a single crystal silicon substrate was selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Magnetron sputtering technology was used, the target material was aluminum, and a layer of Al film with a thickness of 100 nm and (111) texture was grown under the conditions of a target-substrate distance of 80 mm, an argon flow rate of 20 sccm, an RF sputtering power of 100 W, a substrate temperature of room temperature, a working gas pressure of 0.3 Pa, and a sputtering time of 10 min. Then, magnetron sputtering technology was continued in the same chamber, with aluminum and scandium targets as the target materials, and RF sputtering powers of 110 and 90 W respectively. A layer of Al film with a thickness of 300 nm and (0002) texture was grown in situ under the conditions of a target-substrate distance of 80 mm, a nitrogen flow rate of 50 sccm, a substrate temperature of room temperature, a working gas pressure of 0.3 Pa, and a sputtering time of 90 min. 0.7 Sc 0.3 N film. Then, a 150 nm Pt top electrode was prepared by DC magnetron sputtering to obtain a MIM capacitor, and the leakage current of the capacitor was tested using a ferroelectric tester. Figure 2 The Al film with (111) texture is used as the bottom electrode. 0.7 Sc 0.3 The leakage current of the N film capacitor sample is 9×10 -7 A / cm 2 .

[0033] In this comparative example, a single crystal silicon substrate was selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Using DC magnetron sputtering technology, the target material was platinum. A layer of Pt film with a thickness of 100 nm and (111) texture was grown under the conditions of a target-substrate distance of 80 mm, an Ar gas flow rate of 40 sccm, a DC sputtering power of 150 W, a substrate temperature of 100 °C, a working gas pressure of 0.4 Pa, and a sputtering time of 10 min. Then, the silicon substrate deposited with the Pt film was transferred to another RF magnetron sputtering device. The target materials were aluminum and scandium targets. The RF sputtering powers were 170 and 30 W respectively, the target-substrate distance was 80 mm, the nitrogen flow rate was 50 sccm, the substrate temperature was 200 °C, the working gas pressure was 0.4 Pa, and the sputtering time was 80 min. A layer of Al with a thickness of 300 nm and (0002) texture was grown. 0.9 Sc 0.1 N film. Then, in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 20 sccm, the aluminum target sputtering power was 50 W, the substrate temperature was 200 °C, the working pressure was 0.4 Pa, and the sputtering time was 1 min. 0.9 Sc 0.1A 2 nm thick Al film was grown in situ on the surface of the N film. After that, the sputtering was stopped, the argon source was turned off, and 5 sccm of high-purity oxygen was introduced into the same chamber. The gas pressure was maintained at 0.4 Pa, the substrate temperature was 200 °C, and the oxidation time was 1 min. The Al2O3 film with a thickness of about 2 nm was obtained by in-situ oxidation. A 150 nm Pt top electrode was prepared by thermal evaporation to obtain a MIM capacitor, and the leakage current of the capacitor was tested using a ferroelectric tester. Figure 3 After using Al2O3 protective layer, Al 0.9 Sc 0.1 The leakage current of the N sample is 7.1×10 -7 A / cm 2 . Example

[0034] In this embodiment, a single crystal silicon substrate is selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Magnetron sputtering technology is used, the target material is aluminum, and a layer of Al film with a thickness of 100 nm is grown under the conditions of a target-substrate distance of 80 mm, an argon gas flow rate of 20 sccm, a radio frequency sputtering power of 100 W, a substrate temperature of room temperature, a working gas pressure of 0.3 Pa, and a sputtering time of 10 min. Then, magnetron sputtering technology is continued in the same chamber, and the target materials are aluminum and scandium targets. The radio frequency sputtering powers are 110 and 90 W respectively. A layer of Al with a thickness of 300 nm is grown in situ under the conditions of a target-substrate distance of 80 mm, a nitrogen gas flow rate of 50 sccm, a substrate temperature of room temperature, a working gas pressure of 0.3 Pa, and a sputtering time of 90 min. 0.7 Sc 0.3 N film. Then, magnetron sputtering technology was continued in the same chamber, with the nitrogen source turned off, the argon flow rate set to 20 sccm, the aluminum target sputtering power: 50 W, the substrate temperature to room temperature, the working gas pressure to 0.4 Pa, and the sputtering time to 1 min. 0.7 Sc 0.3 A 2 nm thick Al film was grown in situ on the surface of the N film. After that, the sputtering was stopped, the argon source was turned off, and 5 sccm of high-purity oxygen was continued to be introduced into the same chamber. The gas pressure was maintained at 0.4 Pa, the substrate temperature was room temperature, and the oxidation time was 1 min. The Al2O3 film with a thickness of about 2 nm was obtained by in-situ oxidation. Subsequently, a 150 nm Pt top electrode was prepared by DC magnetron sputtering to obtain a MIM capacitor, and the leakage current of the capacitor was tested using a ferroelectric tester. Figure 4 Al film with (111) texture as bottom electrode and Al2O3 protective layer 0.7 Sc 0.3The leakage current of the N film is 9×10 -8 A / cm 2 Compared with the Al2O3 protective layer in Comparative Example 1, 0.7 Sc 0.3 N film, the present invention adopts in-situ growth of Al2O3 protective layer to make Al 0.7 Sc 0.3 The leakage current density of N-film capacitors is reduced by an order of magnitude. Example

[0035] In this embodiment, a single crystal silicon substrate is selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Using RF magnetron sputtering technology, the target material is aluminum. Under the conditions of a target-substrate distance of 80 mm, an argon gas flow rate of 20 sccm, an RF sputtering power of 100 W, a substrate temperature of 200 °C, a working gas pressure of 0.3 Pa, and a sputtering time of 10 min, a layer of Al film with a thickness of 100 nm and a (111) texture is grown. Then, in the same chamber, RF magnetron sputtering technology is continued. The target materials are aluminum and scandium targets. The RF sputtering powers are 170 and 30 W respectively. The target-substrate distance is 80 mm, the nitrogen flow rate is 50 sccm, the substrate temperature is 200 °C, the working gas pressure is 0.4 Pa, and the sputtering time is 80 min. Under the conditions, a layer of Al film with a thickness of 300 nm and a (0002) texture is grown in situ. 0.9 Sc 0.1 N film. Then, in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 20 sccm, the aluminum target sputtering power was 50 W, the substrate temperature was 200 °C, the working pressure was 0.4 Pa, and the sputtering time was 1 min. 0.9 Sc 0.1 A 2 nm thick Al film was grown in situ on the surface of the N film. After that, the sputtering was stopped, the argon source was turned off, and 3 sccm of high-purity oxygen was continued to be introduced into the same chamber. The gas pressure was maintained at 0.4 Pa, the substrate temperature was 200 °C, and the oxidation time was 1 min. The Al2O3 film with a thickness of about 2 nm was obtained by in-situ oxidation. A 150 nm Pt top electrode was prepared by thermal evaporation to obtain a MIM capacitor, and the leakage current of the capacitor was tested using a ferroelectric tester. Figure 5 Al film with (111) texture as bottom electrode and Al2O3 protective layer 0.9 Sc 0.1 The leakage current of the N film is 1×10 -8 A / cm 2 Compared with the non-in-situ method for preparing the Pt bottom electrode and Al 0.9 Sc0.1 N dielectric material, the present invention adopts in-situ growth of Al bottom electrode and Al 0.9 Sc 0.1 The leakage current density of N-film capacitors is reduced by an order of magnitude. Example

[0036] In this embodiment, a single crystal silicon substrate is selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Using RF magnetron sputtering technology, the target material is aluminum. Under the conditions of a target-substrate distance of 100 mm, an argon gas flow rate of 30 sccm, an RF sputtering power of 150 W, a substrate temperature of 100 °C, a working gas pressure of 0.6 Pa, and a sputtering time of 5 min, a layer of Al film with a thickness of 50 nm and (111) texture is grown. Then, in the same chamber, RF magnetron sputtering technology is continued. The target materials are aluminum and scandium targets. The RF sputtering powers are 300 W and 300 W respectively. The target-substrate distance is 100 mm. The nitrogen and argon gas flows are both 20 sccm. The substrate temperature is 100 °C, the working gas pressure is 0.3 Pa, and the sputtering time is 200 min. Under the conditions, a layer of Al film with a thickness of 1500 nm and (0002) texture is grown in situ. 0.6 Sc 0.4 N film. Then, magnetron sputtering technology was continued in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 30 sccm, the aluminum target sputtering power was 70 W, the substrate temperature was 100 °C, the working pressure was 0.6 Pa, and the sputtering time was 2 min. 0.6 Sc 0.4 A 3 nm thick Al film was grown in situ on the surface of the N film. After that, the sputtering was stopped and the argon source was turned off. In the same chamber, 4 sccm of high-purity oxygen was introduced, the gas pressure was maintained at 0.4 Pa, the substrate temperature was 100 °C, and the oxidation time was 2 min. An Al2O3 film with a thickness of about 3 nm was obtained by in-situ oxidation. An 80 nm Au top electrode was prepared by thermal evaporation to obtain a MIM capacitor. The leakage current of the capacitor was tested using a ferroelectric tester. When the electric field strength was 1 MV / cm, the leakage current density was 3×10 -10 A / cm 2 . Example

[0037] In this embodiment, a single crystal silicon substrate is selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Using RF magnetron sputtering technology, the target material is aluminum. Under the conditions of a target-substrate distance of 120 mm, an argon gas flow rate of 50 sccm, an RF sputtering power of 200 W, a substrate temperature of 400 °C, a working gas pressure of 1.0 Pa, and a sputtering time of 20 min, a layer of Al film with a thickness of 200 nm and (111) texture is grown. Then, in the same chamber, RF magnetron sputtering technology is continued. The target materials are aluminum and scandium targets. The RF sputtering powers are 100 and 40 W respectively, the target-substrate distance is 120 mm, the nitrogen and argon gas flows are 30 sccm and 20 sccm respectively, the substrate temperature is 400 °C, the working gas pressure is 0.8 Pa, and the sputtering time is 30 min. Under the conditions, a layer of Al film with a thickness of 50 nm and (0002) texture is grown. 0.8 Sc 0.2 Then, in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 50 sccm, the aluminum target sputtering power was 80 W, the substrate temperature was 400 °C, the working pressure was 0.8 Pa, and the sputtering time was 3 min. 0.8 Sc 0.2 A 5 nm thick Al film was grown in situ on the surface of the N film. After that, the sputtering was stopped and the argon source was turned off. In the same chamber, 2 sccm of high-purity oxygen was introduced, the gas pressure was maintained at 0.4 Pa, the substrate temperature was 400 °C, and the oxidation time was 3 min. An Al2O3 film with a thickness of about 5 nm was obtained. A 100 nm TiN top electrode was prepared by thermal evaporation to obtain a MIM capacitor. The leakage current of the capacitor was tested using a ferroelectric tester. When the electric field strength was 1 MV / cm, the leakage current density was 4.5×10 -8 A / cm 2 .

[0038] The above embodiments are only used to illustrate but not to limit the technical solutions of the present invention. Any technical solutions that do not deviate from the spirit and scope of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for in-situ growing a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode, characterized in that: The method firstly deposits a (111) textured Al metal bottom electrode on a substrate using the same Al metal target in the same chamber, then changes process parameters to achieve in-situ continuous growth of the (111) textured Al bottom electrode film and the (0002) textured wurtzite AlN-based film; secondly, continues to use the Al metal target to in-situ grow an Al metal film on the surface of the wurtzite AlN-based film; finally, in-situ oxidizes the Al metal film into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder; specifically comprises the following steps: Step 1: cleaning the substrate, wherein the substrate is made of sapphire, Si, Ge, GaN or other III-V semiconductor materials; Step 2: The same Al metal target is used in the whole process. In a pure Ar atmosphere, a magnetron sputtering technique is used to deposit an Al bottom electrode film on a substrate. The Al bottom electrode film has a (111) texture structure by adjusting process parameters. Subsequently, in the same chamber, Sc, Y, and B are added as doping element targets. In an Ar and N2 mixed atmosphere or a pure N2 atmosphere, an AlN-based film is in-situ deposited on the Al bottom electrode film by a magnetron sputtering technique. The (111) crystal plane texture of the Al bottom electrode film is used to induce the wurtzite AlN-based film to have a (0002) texture structure. Subsequently, the magnetron sputtering technique is continued in the same chamber. In a pure Ar atmosphere, a metal Al film with a thickness of 2-5 nm is in-situ deposited on the surface of the AlN-based film by a magnetron sputtering technique. Finally, the metal Al film is in-situ oxidized in the same vacuum chamber to transform it into an amorphous, dense Al2O3 thin layer that completely covers the wurtzite AlN-based piezoelectric and ferroelectric film thereunder. The thickness of the Al2O3 thin layer is 2-5 nm.

2. The method for in-situ growing a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode according to claim 1, characterized in that: The thickness of the Al bottom electrode film is 50-200 nm; the thickness of the AlN-based film is 50-1500 nm.

3. The method for in-situ growing a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode according to claim 1, characterized in that: The process parameters include target-substrate distance, ratio of argon to nitrogen, sputtering power, substrate temperature, and working gas pressure; The process parameters for depositing (111) textured Al bottom electrode film are as follows: target-substrate distance 80-120 mm; Ar gas flow rate 20-50 sccm; sputtering power: 100-200 W; substrate temperature room temperature-400 °C; working gas pressure 0.3-1.0 Pa; sputtering time: 5-20 min; The process parameters for depositing (0002) textured wurtzite aluminum nitride-based films are as follows: target-substrate distance 80-120 mm; Ar:N2=(0-20): (20-50) sccm; sputtering power: 50-300 W; substrate temperature room temperature ~ 400 °C; Working gas pressure is 0.4~0.8 Pa; sputtering time: 30-200 min; The specific process parameters for depositing metal aluminum film on the surface of aluminum nitride-based film are as follows: the target material is a single metal aluminum target, the target-substrate distance is 80~120 mm; Ar gas flow rate is 20-50 sccm; sputtering power: 50-80 W; substrate temperature is room temperature~400 ℃; working gas pressure is 0.4~0.8 Pa; sputtering time: 1-3 min.

4. The method for in-situ growing a composite film of a wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode according to claim 1, characterized in that: The in-situ oxidation process is thermal oxidation in which high-purity oxygen is introduced into the vacuum chamber and heated by the sample stage, and plasma oxidation in which the high-purity oxygen introduced into the vacuum chamber is discharged and ionized; The specific process parameters of the in-situ oxidation treatment are: the vacuum chamber is maintained at a negative pressure state below one atmosphere, the substrate temperature is room temperature ~ 400 ° C, and the oxidation time is 1-3 min.

5. A composite film of an in-situ grown wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode, characterized in that: The method is obtained by any one of claims 1 to 4.

6. An application of a composite film of in-situ grown wurtzite aluminum nitride-based film and ultra-thin aluminum oxide protective layer on an aluminum bottom electrode as claimed in claim 5, characterized in that: A top electrode is prepared on the surface of the composite film by thermal evaporation or sputtering to obtain a metal-dielectric-metal MIM structure capacitor.

7. The use of a composite film of in-situ grown wurtzite aluminum nitride-based film and an ultra-thin aluminum oxide protective layer on an aluminum bottom electrode according to claim 6, characterized in that: The top electrode is made of one of the highly conductive metals Au, Pt and Mo; the thickness of the top electrode is 80-150 nm.

Citation Information

Patent Citations

  • Method for sputtering and deposition of aluminum nitride piezoelectric thin film on flexible substrate through room-temperature reaction

    CN102383095A

  • Thin-film piezoelectric resonator manufacturing method, thin-film piezoelectric resonator manufacturing apparatus, thin-film piezoelectric resonator, and electronic component

    CN1757158A

  • Piezoelectric thin film element

    JP2009130182A